Computational modelling of reinforced concrete wall subjected to transformer tank rupture - Mazlan, Abu Seman; Yuantian, Feng; Z. M., Jaini (CSC Press, 2013)
Transformer is one of the vital equipment to provide reliable electricity. The worst of the transformer explosion may lead to the major blackout. Transformer explosion maybe due to, lack of maintenance or the problems inside itself. In the past, transformers were adjacent to each other and without a wall in between at substation. Nowadays, constructing reinforced concrete wall between transformers is in practice as protection precaution. Finite Element Method (FEM) software is used due to the capability of analyzing and simulating reinforced concrete structure subjected to high rate and short duration dynamic loading. The simulation results reveal the crack propagation behavior is identical for the different blast modes. The cracks start to occur at the bottom of the wall on the transformer side. Later follows with the crack propagations on the other side at about one third of the wall height in the curve shape.